Field guide to American antique furniture - Butler, Joseph T.; Johnson, Kathleen Eagen.;Skibinski, Ray. (New York, NY : Facts On File Publications, 1985)
By using a systematic visual approach, this book chronologiically traces the evolution of style in American antique furniture from the 17th century through the early 20th century. The 1700 illustrations are arranged in sequence by type of furniture: chairs; tables; beds; daybeds, sofas, and settees; lift-top chests; chests with movable drawers; desks and bookcases; and miscellaneous. The forms are further divided by style, then by geographic origin from the north to south along the eastern seaboard. In the section on the 19th century; other major furniture centers are treated. Carefully-created line drawings offer the reader a clear means of comparing and identifying furniture styles. As the reader studies the illustrations and the text, the alient characteristics of each style will emerge and comparisons among styles can also be made. Although cabinetmakers sometimes combined elements from several styles in the design of one piece of furniture, for instructive purposes examples shown here are designed to illustrate style in its purest form. The framework for presenting historical American furniture styles has been based on the finest examples of the period. Individual pieces have been identified as specifically as possible, including maker, working dates, place of origin, and date, when known. Because certain furniture forms have been made over a number of centuries, they are difficult to date by means of stylistic attributes. These long-lived vernacular forms of furniture are treated, therefore, in the time period when they first developed. While the guide is designed to provide the information needed to identify any major style of antique furniture popular in America before World War l, it does not, and cannot, treat the subject of authenticity. That sort of knowledge can only be acquired through frequent and thorough examination of the actual furniture. For a more in-depth look at fine examples of furniture, the reader is strongly advised to visit the major collections listed on page 366. This book can help educate the eye to distinguish differences in styles, but there is no substitute for seeing the furniture first hand.
Preface -- Anatomy of furniture -- Part One. History of American furniture: Origins of American furniture -- The 17th century -- The William and Mary style -- The Queen Anne style -- The Chippendale style -- Windsor furniture -- Germanic furniture -- New influences on furniture design -- American Neoclassicism- the federal style -- The empire style -- Late classicism and the Restauration style -- Shaker furniture -- The Gothic and Elizabethan revival styles -- The Rococo revival style -- The Louis XVI revival style -- The renaissance revival style -- The Victorian renaissance or Neo-Grec style -- The colonial revival style -- Innovative furniture -- Exotic and eclectic -- Design reform -- Part Two. Field guide to American antique furniture: Chairs -- Tables -- Beds -- Daybeds, sofas, benches, settees, Lift-top chests -- Chests of drawers -- Desks and bookcases -- Miscellaneous -- Sources of furniture illustrated -- Outstanding collections of American furniture -- Selected bibliography -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: FURNITURE